'What are you waiting for, Diggers?' The ANZAC image in Commando comics - Philip Cass (Asia Pacific Network, 2017)
For generations of Australians and New Zealanders, Commando comics have provided a consistent image of their ancestors at war. The image is one of men, who are inevitably tall, bronzed, shirtless, contemptuous of authority and their ability, as warriors such—in memory at least—that their mere presence on the battlefield is enough to have the Germans crying ‘Donner und blitzen!’, and the Italians ‘Sapristi!’ or the Japanese ‘Aieee!’ But how accurate is this depiction of Australians and New Zealanders? How well does a Scottish comic—often employing artists from Argentina and other countries—portray the ANZACS? And how did a Scottish comic come to dominate the image of Australians and New Zealanders at war for so long?